2020
DOI: 10.3389/fonc.2020.00838
|View full text |Cite
|
Sign up to set email alerts
|

CT-Imaging Based Analysis of Invasive Lung Adenocarcinoma Presenting as Ground Glass Nodules Using Peri- and Intra-nodular Radiomic Features

Abstract: Objective: To evaluate whether radiomic features extracted from intra and peri-nodular lesions can enhance the ability to differentiate between invasive adenocarcinoma (IA), minimally invasive adenocarcinoma (MIA), and adenocarcinoma in situ (AIS) manifesting as ground-glass nodule (GGN). Materials and Methods: This retrospective study enrolled 120 patients with a total of 121 pathologically confirmed lung adenocarcinomas (85 IA and 36 AIS/MIA) from January 2015 to May 2019. The recruited patients were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…CT-based radiomics providing a non-invasive and low-cost analysis technique for tumor property evaluation based on image data has been widely applied (26). The radiomics-based machine learning model can analyze and process CT images in the gray level as well as individual level (27). In the training stage, it is capable of learning from experiential data and hence could discover the general trend of those (priori knowledge).…”
Section: Discussionmentioning
confidence: 99%
“…CT-based radiomics providing a non-invasive and low-cost analysis technique for tumor property evaluation based on image data has been widely applied (26). The radiomics-based machine learning model can analyze and process CT images in the gray level as well as individual level (27). In the training stage, it is capable of learning from experiential data and hence could discover the general trend of those (priori knowledge).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the GLRLM and NGLDM texture analysis can assess the heterogeneity of the lesion (27,28). Wu et al (29) reported that the GLRLM textural feature could be useful in differentiating the invasiveness of lung adenocarcinoma. The study by Hoshino et al (28) presented that NGLDM_Coarseness was correlated with the real miR-1246 expression in the serum of esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al. ( 29 ) reported that the GLRLM textural feature could be useful in differentiating the invasiveness of lung adenocarcinoma. The study by Hoshino et al.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the imbalanced sample distribution between COVID-19 and non-COVID-19 patients (the number of non-COVID-19 patient is lower than the number of COVID-19 patients), synthetic minority over-sampling technology [ 36 40 ] was used to generate synthetic non-COVID-19 patient samples in the training set so that a synthetically class-balanced training set could be achieved prior to training the models in this study. Briefly, for each minority sample “a” in the non-COVID-19 patient group, the synthesis strategy was applied to randomly select a minority sample “b” from its nearest neighbors.…”
Section: Methodsmentioning
confidence: 99%